2019
DOI: 10.1002/mp.13675
|View full text |Cite
|
Sign up to set email alerts
|

Fully automatic liver attenuation estimation combing CNN segmentation and morphological operations

Abstract: Purpose Manually tracing regions of interest (ROIs) within the liver is the de facto standard method for measuring liver attenuation on computed tomography (CT) in diagnosing nonalcoholic fatty liver disease (NAFLD). However, manual tracing is resource intensive. To address these limitations and to expand the availability of a quantitative CT measure of hepatic steatosis, we propose the automatic liver attenuation ROI‐based measurement (ALARM) method for automated liver attenuation estimation. Methods The ALAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
0
24
1
Order By: Relevance
“…However, these methods are not accurate enough for fully automated liver segmentation without user interaction ( 13 14 15 16 ). Recently, deep learning based on a convolutional neural network (CNN) has emerged as a method for image-based organ segmentation ( 12 17 18 ). Previous studies reported promising results of deep learning algorithms (DLAs)-based liver segmentation using CT images ( 7 19 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are not accurate enough for fully automated liver segmentation without user interaction ( 13 14 15 16 ). Recently, deep learning based on a convolutional neural network (CNN) has emerged as a method for image-based organ segmentation ( 12 17 18 ). Previous studies reported promising results of deep learning algorithms (DLAs)-based liver segmentation using CT images ( 7 19 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Automated CT-and MRI-based Assessment of Liver Fat Automated assessment of CT liver Hounsfield unit values and MRI PDFF maps has emerged using deep learning-based algorithms (Fig E1 [online]) for liver fat quantification (89)(90)(91)(92)(93)(94)(95). Fully automated liver segmentation may increase objectivity and reproducibility, avoiding bias introduced by human analysts (89).…”
Section: Future Trendsmentioning
confidence: 99%
“…However, the u-net architecture proposed by Ronneberger et al (Ronneberger et al 2015) demonstrated fast and precise segmentation without the need for a large data set. DNNs have, as a result, become the state-of-the-art method for segmentation in biomedical image classification (Shao et al 2019;Huo et al 2019). Instead of requiring minutes to generate a segmentation prediction, CNNs can produce an output in the matter of seconds.…”
Section: Rationale For Deep Learning Approachmentioning
confidence: 99%